PROBLEMATIKA INDISIPLINER PESERTA DIDIK LAKI-LAKI KELAS II SD SUPRIYADI DITINJAU DARI COOPERATIVE LEARNING - Rida Kurniawati; Ngurah Ayu Nyoman Murniati; Ervina Eka Subekti (STKIP Subang, 2023)
This research is motivated by the disciplinary problems of male students in cooperative learning activities. The purpose of this research is to find out the problems of disciplinary actions by male students at SD Supriyadi Semarang in cooperative learning and their solutions. The subject of this study was class 2 A students. The approach used was descriptive qualitative. Data collection techniques through observation, interviews, and documentation. Test the credibility of the data through triangulation. Data will be analyzed through data reduction, data presentation and drawing conclusions. The results of the research analysis show that male students take disciplinary action when utilizing the phenomenon of cooperation in learning, thereby disrupting the ongoing teaching and learning activities of other students, especially women. In addition, the results of group learning on male students tend to be lower than female students. Male students get an average score of 64.5 while female students get an average score of 83.3. Therefore, the teacher should make regulatory procedures to motivate students, and group students without discriminating against them.